The Effect of Protection for Investors, Sharia Financial Accounting Standards, Good Corporate Governance on Audit Quality and Their Implications on Profit Quality of Sharia Commercial Banks in Indonesia - Slamet Wahyudi (Budapest International Research and Critics University, 2022)
This study aims to estimate and analyze the effect of investor protection, Islamic financial accounting standards, and good corporate governance on audit quality and their implications for earnings quality, either partially or jointly. The sample used is 11 Islamic commercial banks in Indonesia in 2013-2019 so that the observed data are 77. The research method used is a quantitative research method with panel data regression analysis. The results show that, in the first model, partial protection for investors has a significant positive effect, Islamic financial accounting standards have a significant positive effect, and good corporate governance has a significant positive effect on audit quality. Taken together, investor protection, Islamic financial accounting standards, and good corporate governance have a significant effect on audit quality b=0.837185, so the model equation is KAU = [Ci + 0.837185] + 0.182762 * PBI + 0.218712 * SAS + 0.309210 * GCG. In the second model, partial protection for investors has an insignificant negative effect, Islamic financial accounting standards have a significant positive effect, good corporate governance has a significant positive effect, and audit quality has a significant positive effect. Taken together, investor protection, sharia financial accounting standards, good corporate governance and audit quality have a significant effect on earnings quality, so the equation of the model is KALA = [Ci + 0.492812] – 3.940632 * PBI + 0.582245 * SAS + 1.357672 * GCG +0.966662 * YOU.